Asbestos and Asbestos-related Diseases in Vietnam: In reference to the International Labor Organization/World Health Organization National Asbestos Profile - Van Hai Pham; Thi Ngoc Lan Tran; Giang Vinh Le; Mehrnoosh Movahed; Ying Jiang; Nguyen Ha Pham; Hisashi Ogawa; Ken Takahashi (Elsevier, 2013)
This paper describes progress on formulating a national asbestos profile for the country of Vietnam. The Center of Asbestos Resource, Vietnam, formulated a National Profile on Asbestos-related Occupational Health, with due reference to the International Labor Organization/World Health Organization National Asbestos Profile. The Center of Asbestos Resource was established by the Vietnamese Health Environment Management Agency and the National Institute of Labor Protection, with the support of the Australian Agency for International Development, as a coordinating point for asbestos-related issues in Vietnam. Under the National Profile on Asbestos-related Occupational Health framework, the Center of Asbestos Resource succeeded in compiling relevant information for 15 of the 18 designated items outlined in the International Labor Organization/World Health Organization National Asbestos Profile, some overlaps of the information items notwithstanding. Today, Vietnam continues to import and use an average of more than 60,000 metric tons of raw asbestos per year. Information on asbestos-related diseases is limited, but the country has begun to diagnose mesothelioma cases, with the technical cooperation of Japan. As it stands, the National Profile on Asbestos-related Occupational Health needs further work and updating. However, we envisage that the National Profile on Asbestos-related Occupational Health will ultimately facilitate the smooth transition to an asbestos-free Vietnam.